LINGUOPRAGMATICS OF INTERACTION IN THE GENRE OF BUSINESS PRESENTATION - Natalya Yu. Sorokoletova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
The article is devoted to the description of the discursive and pragmatic parameters of interaction in the genre of business presentation. As a rhetorical genre of business discourse, the presentation is characterized by its own scenario of communicative behavior and aims at informing the audience about innovations (ideas, projects, brands, goods, services) and providing their commercial promotion by influencing people (potential customers) and encouraging them to take actions beneficial to the company. According to the study the model of business presentation genre includes its obligatory participants (addressees and addressers); the specific interaction between them is determined by informativity and persuasiveness of the communication. The implementation of the interaction between the addresser and addressee is carried out through specific tactics of communicative dialogization, actualized by a number of discursive and pragmatic means (general/special questions, cohesion and coherence techniques, imperatives), as well as etiquette speech acts that organize and maintain contact throughout the communication. The linguistic-and-pragmatic analysis revealed that in the business presentations under study etiquette speech acts of greeting, appeal, gratitude, farewell create polyfunctional speech units (sometimes a sequence of them) producing the illusion of interaction (pseudo-dialogue): the addresser, as an agent of communication, attracts and captures the attention of the addressees and their interest to the topic of the presentation, monitors the process of communication and provides its positive tonality. The choice of linguistic and pragmatic means is determined by the purpose of the presentation and is modelled by the intentions of the addresser.